Implementasi Kurikulum Pesantren pada Sekolah Formal (Studi Kasus: SMP Muhammadiyah Plus Klaten Utara) - Gunagraha, Shindid; Khuriyah, Khuriyah (ISLAMIKA, 2024)
The purpose of this study is to examine how the implementation of the pesantren curriculum is integrated into formal educational institutions, especially in the Muhammadiyah Plus North Klaten Junior High School in designing the curriculum as a form of process of fostering, educating and encouraging students to underlie every behavior with good moral values or character. Formal School Education Curriculum to the Islamic Boarding School Curriculum In strengthening character education, data collection is carried out through observation, interviews and documentation. After data processing, the findings are presented in a descriptive form, and conclusions are formed from the data using source triangulation and methods. The results of the study show that there is an implementation of a formal education curriculum development model by collaborating with the values of the pesantren education curriculum which can be a solution in strengthening the morals of students. Thus, the curriculum becomes a tool in education that contains systematic and dynamic planning to achieve educational goals that have an impact on the social environment and society and are able to answer the challenges of the times.